The surgical tactics peculiarities at brain giant arterial aneurysms - Khinikadze, M. R. (Ukrainian Neurosurgical Journal, 2007)
The problems of surgical treatment efficacy increasing in patients with brain vessels giant aneurysms were discussed, criteria, that allowed to apply surgical methods at such pathology, were determined.